Remains of the Bumi Ayu Site as Evidence of Religious Tolerance During the Sriwijaya Independence Period: Peninggalan Situs Bumi Ayu, Nilai Religi Peninggalan Situs Bumi Ayu, Bentuk Toleransi Beragama Pada Masyarakat Bumi Ayu - Dhanty, Dhanty Rahmallah Agustina; LR. Retno Susanti (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
“Remains of the Bumi Ayu Site as Evidence of Religious Tolerance During the Sriwijaya Independence Period” according to the study. The problem in this study is how the form of the remains of the Bumi Ayu site during the Sriwijaya Independence period, what are the religious values on the remains of the Bumi Ayu temple site and what are the forms of religious tolerance in the Bumi Ayu community during the Sriwijaya Independence era. The goal of the study is to learn more about the issues mentioned above. The research approach employed is the historical method, which includes heuristics, source critique, interpretation, historiography, and interviews, as well as literature study. While theology, archaeological, and pluralism techniques are employed. This study looks at the Bumi Ayu bathing Site, Buddhist remains at the Bumi Ayu Bathing site, which consists of Temples 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10, as well as statues in the temple above. Religious values in the heritage of the Bumi Ayu site and forms of religious tolerance in the Bumi Ayu people during the Sriwijaya period. The findings revealed that at the Bumi Ayu Bathing site there were three different religious sects namely Siwais Hinduism, Tantrayana Hinduism, and Buddhism. The three religious are proven by the discovery of statues from each religious relic. So that in the Bumi Ayu Bathing complex it is believed that there has been religious tolerance among the people around the Bumi Ayu Bathing site.